Musical salon culture in the long nineteenth century - Bunzel, Anja ca. 20./21.Jh; Loges, Natasha ca. 20./21. Jh (The Boydell Press, 2019)
This collection explores the idea of music in the salon during the long nineteenth century, both as a socio-cultural phenomenon, and as a source of artistic innovation and exchange. Drawing on a wide range of scholarly approaches, this book uses the idea of the salon as a springboard to examine issues such as gender, religion, biography and performance; to explore the ways in which the salon was represented in different media; and to showcase the heterogeneity of the salon through a selection of case studies. It offers fresh considerations of familiar salons in large cultural centres, as well as insights into lesser-known salons in both Europe and the United States. Bringing together an international group of scholars, the collection underscores the enduring impact of the European musical salon. - ANJA BUNZEL holds a research position at the Czech Academy of Sciences. She gained her PhD in Musicology from Maynooth University and has published on Johanna Kinkel and nineteenth-century salon culture in both English and German. NATASHA LOGES is Head of Postgraduate Programmes at the Royal College of Music, London. Her publications include Brahms in the Home and the Concert Hall (Cambridge, 2014) and Brahms and his Poets (Boydell Press, 2017). She is a pianist, broadcaster and critic. (Klappentext)